A potential new role of ATM inhibitor in radiotherapy: suppressing ionizing Radiation-Activated EGFR. (2nd April 2020) - Tang, Siyuan; Li, Zhentian; Yang, Lifang; Shen, Liangfang; Wang, Ya
Abstract: Purpose: Although EGFR inhibitor (EGFRi) is used in cancer therapy to suppress tumor growth and resistance to treatment including radiotherapy, EGFRi resistance frequently developed, which significantly reduced treatment outcomes. Therefore, developing alternative approaches for EGFRi is of great importance. Based on our recent observation that ATM inhibitor (ATMi) efficiently inhibited ionizing radiation (IR)-induced EGFR activation in mouse embryo fibroblasts (MEF), the main purpose of this study is to determine whether ATMi could inhibit IR-induced EGFR activation in human tumor cell lines and explore its potential in EGFRi-alternative therapies. Materials and methods: We compared the effects of ATMi, EGFRi individually or in combination on IR-induced EGFR phosphorylation, cell growth and radio-sensitization in nine human tumor cell lines including lung adenocarcinoma (A549 and H358), glioblastoma (LN229), cervical cancer (HeLa), colorectal carcinoma (SW480 and HCT116) and nasopharygeal carcinoma (5–8 F, 6–10B and HK1) cell lines. In addition, we detected the effects of ATMi, EGFRi alone or both on the efficiency of non-homologous end-joining (NHEJ) and homologous recombination (HR) using I-SceI –GFP based NHEJ or HR reporter cell lines. Results: Compared to EGFRi treatment, ATMi treatment decreased IR-induced EGFR phosphorylation, suppressed growth and increased IR sensitization in tested cell lines at a similar or even more efficient level. Combining ATMi and EGFRi did not significantly increased the effects on these phenotypes as ATMi treatment alone. Also, similar to ATMi, EGFRi mainly reduced the efficiency of HR but not NHEJ although combining ATMi and EGFRi further inhibited the HR efficiency. Conclusions: Our study demonstrates that ATMi can function like EGFRi in human tumor cells to inhibit tumor cell growth and sensitize the tumor cells to IR, suggesting that ATMi treatment as an alternative approach may exert anticancer effects on EGFRi-resistant tumor cells and facilitate radiotherapy.